Green Conservatism dalam Pemikiran Roger Vernon Scruton (1944-2020) - Abdul Rahman Siregar; Junaidi Junaidi; Husna Sari Siregar (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2024)
This article examines the concept of green conservatism in the thought of Roger Vernon Scruton (1944-2020), a prominent conservative philosopher. The research aims to analyze the intellectual stimulus that gave birth to the idea of green conservatism and evaluate its main principles. The results show that Scruton's green conservatism stems from his personal experience and his belief in the importance of environmental preservation through local approaches and respect for tradition. The main stimuli that influenced Scruton's thinking include his complicated relationship with his father, his experiences in Paris during the 1968 student riots, and his decision to leave academia to focus on writing and agriculture. Scruton integrated traditional conservative principles with environmental concerns through the concepts of oikophilia (love of home), subsidiarity, localism, and cultural and historical preservation. With this approach, Scruton challenges the dominant narrative in environmentalism and offers a new perspective that emphasizes the importance of local awareness and personal responsibility in environmental conservation.